Income disparity and utilization of cardiovascular preventive care services among U.S. adults - Andi Shahu; Victor Okunrintemi; Martin Tibuakuu; Safi U. Khan; Martha Gulati; Francoise Marvel; Roger S. Blumenthal; Erin D. Michos (Elsevier, 2021)
Objective: Associations between income disparity and utilization of cardiovascular disease (CVD) preventive care services, such as receipt of lifestyle advice and screening for CVD risk factors in populations with and without CVD, are not well understood. The purpose of this study was to evaluate associations between income and utilization of CVD-preventive services among U.S. adults. Methods: We included adults ≥18 years with and without CVD from the 2006 to 2015 Medical Expenditure Panel Survey. We categorized participants as high-income (>400% of federal poverty level [FPL]), middle income (200-400% of FPL), low-income (125-200% of FPL) and very low (VL)-income (<125% of FPL). We used logistic regression to compare the likelihood of receiving CVD-preventive services by income strata, adjusting for sociodemographic factors and comorbidities. Results: The study included 185,081 participants (representing 194.6 million U.S. adults) without CVD, and 32,862 participants (representing 37 million U.S. adults) with CVD. VL-income adults without CVD were less likely than high-income adults to have blood pressure measured within past 2 years [odds ratio [OR] 0.41 (95% confidence interval [CI] 0.37-0.45)] or cholesterol levels checked within past 5 years [0.36 (0.33-0.38)] or receive counseling about diet modifications [0.77 (0.74-0.81)], exercise [0.81 (0.77-0.85)], or smoking cessation [0.71 (0.63-0.79)] within past year. VL-income adults with CVD were also less likely to have blood pressure [0.32 (0.22-0.46)] or cholesterol [0.33 (0.26-0.42)] checked and receive counseling about exercise [0.84 (0.76-0.93)] or smoking cessation [0.78 (0.61-0.99)]. Additional subgroup analyses restricted to participants who had seen a healthcare provider within the preceding 12 months, as well as secondary analyses stratified by sex, race and ethnicity, showed similar disparities between high-income and VL-income participants. Conclusions: VL-income adults were less likely to be screened for CVD risk factors or receive CVD-prevention counseling than high-income adults, regardless of CVD status. More work must be done to reduce disparities in access to and utilization of CVD-preventive services among adults in different income groups.